274 QRS DURATION AND Q-TC INTERVAL DO NOT CORRELATE WITH SERUM MARKER OF MYOCARDIAL FIBROSIS IN PATIENTS WITH ADVANCED SYSTOLIC HEART FAILURE. Issue 1 (1st January 2007) - Sadhu, A.; Phisitkul, K; Puga, L.; Simoni, J.; Pierce, M.; Roongsritiong, C.
Abstract : Purpose: QRS duration is currently used to select patients with advanced systolic heart failure (HF) for device therapy. Q-Tc prolongation has long been associated with increased risk of ventricular arrhythmias. We hypothesized that the degree of fibrosis within the myocardium may influence QRS duration and Q-Tc interval in patients with advanced systolic HF. Methods: Thirty-six patients with systolic HF and EF < 35% were enrolled. The 12-lead ECGs were reviewed for QRS duration and Q-Tc determination. In general, computerized values were used unless they were significantly different from the manually measured values. Serum marker of fibrosis, carboxy-terminal of the procollagen type I (PICP), was determined by a commercial ELISA kit (Takara Inc.). Data are presented as mean ± standard deviation. Correlation between QRS duration and Q-Tc interval to PICP levels and selected echocardiographic (ECHO) parameters of the left ventricle were assessed. A p value < .05 was considered statistically significant. Results: The mean left ventricular ejection fraction (EF), QRS duration, and Q-Tc interval were 23.0 ± 5.4%, 125.8 ± 33.9 milliseconds, 487.6 ± 42.0, respectively. Mean PICP level was 997.4 ± 455.1 ng/mL. Conclusions: In this small study of patients with advanced systolic HF, the degree of myocardial fibrosis as determined by serum levels of PICP did not correlate with QRS duration or Q-Tc interval. Q-Tc, on the other hand, significantly correlated with EF.